Contributions of Luis F. de Armas to Hispaniolan arachnids (Arthropoda: Arachnida): over 40 years of constant work - Santos, Gabriel De Los; Carrero-Jiménez, Solanlly (Zootaxa, 2025)
Joining the celebration of Luis F. de Armas 80th birthday, we present a concise overview of his contributions to the knowledge of Hispaniolan arachnids. To do this, we reviewed different checklists and catalogs, and his extensive literature about these arthropods on this island.